2022
DOI: 10.1186/s41935-022-00276-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of direct analysis in real-time mass spectrometry (DART-MS) in forensic science: a comprehensive review

Abstract: Background As the rate of crime is constantly increasing, the workload on the forensic analyst also piles up. The availability of a limited number of seized samples makes it crucial to directly analyze the sample, thereby preventing wastage in the prior steps of sample preparation. Due to such needs, the forensic community is consistently working on broadening the usage of direct analysis in real-time mass spectrometry (DART-MS). DART-MS is a relatively new technique for rapid mass spectral ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…The same impurity spots could also be identified when β-naphthol was replaced by either phenol or resorcinol (Figure S4), suggesting that they could originate from aniline or its diazotized product. Direct analysis in real time (DART)-MS , was used to analyze these species by scraping the silica particles containing the bands of these species and directly introducing them to the sample inlet. It was found that both impurities had the same molecular mass (specifically m / z 198.1028 and 198.1029 for impurities #1 ( R f = 0.58) and #2 respectively ( R f = 0.34)).…”
Section: Investigation Of the Cause Of Varying Color Darknessmentioning
confidence: 99%
“…The same impurity spots could also be identified when β-naphthol was replaced by either phenol or resorcinol (Figure S4), suggesting that they could originate from aniline or its diazotized product. Direct analysis in real time (DART)-MS , was used to analyze these species by scraping the silica particles containing the bands of these species and directly introducing them to the sample inlet. It was found that both impurities had the same molecular mass (specifically m / z 198.1028 and 198.1029 for impurities #1 ( R f = 0.58) and #2 respectively ( R f = 0.34)).…”
Section: Investigation Of the Cause Of Varying Color Darknessmentioning
confidence: 99%
“…2021 a prototype of a new Inverted Library-Search Algorithm (ILSA) that enhances presumptive identifications of mixture components using a series of in-source collision-induced dissociation mass spectra collected through DART-MS ( https://github.com/asm3-nist/DART-MS-DST ) [ 1018 ]; creation and release of the new NIST DART-MS Forensics Database and the steps taken to automate the data evaluation process [ 1019 ]; 2022 review of the application of DART-MS in forensic science [ 1020 ].…”
Section: Instrument Focusmentioning
confidence: 99%
“…The ionization mechanism of DART is that a neutral or inert gas (e.g., nitrogen or helium) is discharged at atmospheric pressure to generate excited atoms, which are rapidly heated and accelerated by an electric field to desorb and instantaneously ionize the compound to be measured on the sample surface. The connection of the DART source to HRMS allows direct analysis of the sample in real time [81]. Dane et al used DART in negative-ion mode with time-of-flight MS to characterize n-alkanes with larger carbon numbers (C > 18), producing mainly [M + O 2 ] −• and with less fragmentation, achieving soft ionization of hydrocarbons to some extent [82].…”
Section: Chemical Ionization-based Soft Ionizationmentioning
confidence: 99%